(untitled) (Journal of Economic Research & Business Administration, 2021)
Currently, there is a significant intraregional socio-economic differentiation between the regions of the Republic of Kazakhstan. Inequality in the socio-economic development of the regions, which significantly impedes the implementation of socio-economic policy, the efficiency of the country’s economy, and the sustainable development of the country. The solution to the existing problems of socioeconomic asymmetry of regions consists in the formation and application of a systematic approach to the management of socio-economic space, the use of modern tools of regional policy, the creation of a system of regulation of the regional market based on the concentration of private investment resources, which will smooth out the asymmetry of territories both throughout the country and within individual regions. In this regard, there is a need to improve the regional policy of territorial development, which can reduce the scale of intraregional differentiation of territories. The purpose of the article is to prevent, assess differentiation and suggest ways to reduce it, the consequences of which lead to the emergence of problem areas, increasing regional inequality. The article analyzes the problems of socio-economic inequality of the regions, the regions are grouped by levels of development, and suggests measures to improve the regional policy of the state. To study the problems of inequality, the methodology of system analysis, methods of comparative analysis, and statistical methods were used. The empirical base of the study was made up of data from the National Bureau of Statistics of the Republic of Kazakhstan. Key words: region, inequality in socio-economic development, differentiation, gross regional product, socio-economic development of the region.